On the Economic Interpretation and Measurement of Optimal Capacity Utilization with Anticipatory Expectations - Morrison, Catherine J. (Review of Economic Studies, 1985)
This study builds on recent research giving the notion of capacity utilization clearer economic foundations. In this research optimal output Y* is defined as the minimum point on the firm's short-run average total cost curve, and capacity utilization is then computed as CU=Y/Y*, where Y is actual output. Here I extend these concepts to include adjustment costs due to changes in the stock of capital, and nonstatic expectations of future output demand and input prices. The more general notion of CU is shown to depend on the shadow values of the firm's quasifixed inputs, and is decomposed to isolate the effects of anticipatory expectations. An empirical comparison is then made between traditional indices and alternative economic CU measures, using annual U.S. manufacturing data 1954-80. The calculated indices exhibit plausible patterns, which can be interpreted as the effects of nonstatic expectations and adjustment costs.